A Meloidogyne graminicola Pectate Lyase Is Involved in Virulence and Activation of Host Defense Responses - Chen, Jiansong; Li, Zhiwen; Lin, Borong; Liao, Jinling; Zhuo, Kan (Frontiers in Plant Science, 2021)
Plant-parasitic nematodes secrete an array of cell-wall-degrading enzymes to overcome the physical barrier formed by the plant cell wall. Here, we describe a novel pectate lyase gene Mg-PEL1 from M. graminicola. Quantitative real-time PCR assay showed that the highest transcriptional expression level of Mg-PEL1 occurred in pre-parasitic second-stage juveniles, and it was still detected during the early parasitic stage. Using in situ hybridization, we showed that Mg-PEL1 was expressed exclusively within the subventral oesophageal gland cells of M. graminicola. by using in situ hybridization. MoreoverThe yeast signal sequence trap system revealed that it possessed an N-terminal signal peptide with secretion function., according to the yeast signal sequence trap system. Recombinant Mg-PEL1 exhibited hydrolytic activity toward polygalacturonic acid. Rice plants expressing RNA interference vectors targeting Mg-PEL1 showed an increased resistance to M. graminicola. In addition, using an Agrobacterium-mediated transient expression system and plant immune response assays, we demonstrated that the cell wall localization of Mg-PEL1 was required for the activation of plant defense responses, including programmed plant cell death, reactive oxygen species accumulation and expression of defense-related genes. Taken together, our results indicated that Mg-PEL1 can could enhance the pathogenicity of M. graminicola as well as has an ability inand inducing induce plant immune responses during nematode invasion into plants or migration in plants, . This providing provides a new insight into the function of pectate lyases in the interaction between plants-parasitic nematodess interaction and host plantsparasitism.